Implementation of the Concept of Progressive Islamic Education in Muhammadiyah and Its Challenges in the Age of Social Media - Andri Moewashi Idharoel Haq (Universitas Muhammadiyah Malang, 2024)
This research aims to explore the implementation of the concept of Progressive Islam in Islamic education within the Muhammadiyah, with a focus on the utilization of social media and information technology. The research method involves literature review, a survey of 300 students at Muhammadiyah University Sukabumi in West Java, including interviews with lecturers and Muhammadiyah figures. The results indicate that the concept of Progressive Islam has widely permeated among students and the community, especially through social media and the internet, and has made a positive contribution to strengthening religious identity and understanding of Islamic teachings. This article argues that an open approach to technology is crucial in expanding access to Islamic education, as well as its implications in shaping a generation that is more adaptive and responsive to the developments of the times. This research contributes to providing a deeper understanding of the implementation of the concept of Progressive Islam in Islamic education in the digital era, and highlights the important role of social media and information technology in strengthening religious identity and progressive values in society.